If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + -26)(a + 144) = 0 Reorder the terms: (-26 + a)(a + 144) = 0 Reorder the terms: (-26 + a)(144 + a) = 0 Multiply (-26 + a) * (144 + a) (-26(144 + a) + a(144 + a)) = 0 ((144 * -26 + a * -26) + a(144 + a)) = 0 ((-3744 + -26a) + a(144 + a)) = 0 (-3744 + -26a + (144 * a + a * a)) = 0 (-3744 + -26a + (144a + a2)) = 0 Combine like terms: -26a + 144a = 118a (-3744 + 118a + a2) = 0 Solving -3744 + 118a + a2 = 0 Solving for variable 'a'. Factor a trinomial. (-144 + -1a)(26 + -1a) = 0Subproblem 1
Set the factor '(-144 + -1a)' equal to zero and attempt to solve: Simplifying -144 + -1a = 0 Solving -144 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '144' to each side of the equation. -144 + 144 + -1a = 0 + 144 Combine like terms: -144 + 144 = 0 0 + -1a = 0 + 144 -1a = 0 + 144 Combine like terms: 0 + 144 = 144 -1a = 144 Divide each side by '-1'. a = -144 Simplifying a = -144Subproblem 2
Set the factor '(26 + -1a)' equal to zero and attempt to solve: Simplifying 26 + -1a = 0 Solving 26 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -1a = 0 + -26 Combine like terms: 26 + -26 = 0 0 + -1a = 0 + -26 -1a = 0 + -26 Combine like terms: 0 + -26 = -26 -1a = -26 Divide each side by '-1'. a = 26 Simplifying a = 26Solution
a = {-144, 26}
| 5m+7=142 | | 7+x=-17 | | 5n^2-15=-10n | | -18=1-3a-4 | | lg(3x-2)=-1 | | 4x=8+y | | (9x+6)-(4x^2+2x+3)= | | 6.5=2.5r-12 | | (2y-10)+2x=82 | | -30=p/12 | | y=3x^2-5x+1 | | 25=-2w | | 8v=2*(4v+2) | | 4x^3+16x=0 | | 25v-4v+8=4 | | 2y-10+2x=p | | y=2x^2+4x+2 | | 4r-3r-1=4 | | 7x-3*2=x | | 0=-16t^2+76t+46 | | 4x+x-4=2 | | 2x-5/2-4/5 | | 9-7(2)^3/(-8) | | 8-3(3)^3/(-27) | | 0=-16t^2+26t+100 | | 15-2.5h=4h | | (2+2)^2/(5-3)^2 | | 2b+3b-13=-3 | | 2n-3n+1=5 | | b^2-4ac=-3 | | 3x+2=3(x+8) | | 21x-28-15x-25=7x-70 |